Parent-Child Relationship and Smartphone Addiction: The Role of Self-Control and Fear of Missing Out as Mediators - Suprapto, Maria Helena; Setiasih, Setiasih; Siaputra, Ide Bagus (Universitas Ahmad Dahlan, 2024)
This research aimed to analyze the phenomenon of smartphone addiction among Junior High School students, with a specific focus on parent-child relationship, self-control, and Fear of Missing Out (FOMO). In addition, data was collected through Smartphone Application-Based Addiction Scale (SABAS), Network of Relationship Inventory – Relationship Quality Version (NRI-RQV), Brief Self-Control Scale (BSCS), and FOMO Scale. A total of 681 Adolescents aged 12-15 from Junior High Schools in Surabaya or Sidoarjo were sampled using convenience sampling, while Structural Equation Modeling (SEM) was adopted for data analysis. The results showed that there was a direct and indirect impact of adolescents' relationship on the tendency to become addicted to smartphones. Furthermore, closeness and incompatibility of adolescents with fathers and mothers indirectly influenced smartphone addiction, mediated by self-control and FOMO, respectively. This reported the importance of enhancing warm relationship to reduce the risk of smartphone addiction in adolescents.